Pengaruh Penggunaan Konten Hiburan Tiktok terhadap Tingkat Stres di Kalangan Mahasiswa - Wardah, Jihan Syalina; Nugroho, David Rizar; Ulya, Enden Darjatul; Mulyono, Mulyono (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
This study aims to analyze the influence of entertainment content consumption on TikTok toward the stress levels of university students. TikTok has become one of the most frequently used social media platforms among young adults, offering entertainment, distraction, and emotional relief. Meanwhile, academic stress is a common issue among students due to heavy coursework, deadlines, and pressure to perform. This research uses a quantitative method with a survey distributed to 100 active university students aged 18–24 who own a TikTok account and consume entertainment content such as comedy, challenges, and viral videos. Data were analyzed using descriptive statistics and simple linear regression. The results show that the overall frequency of using TikTok for entertainment is very high (mean = 4.26), while the level of academic stress also falls into the high category (mean = 4.06). Regression analysis indicates that TikTok entertainment content significantly affects students’ stress levels (p < 0.001). Result found is positive, meaning higher TikTok usage is associated with higher stress. The significance value based on the simple linear regression coefficient table is 0.000 < 0.05, so it can be concluded that the variable Use of TikTok Entertainment Content (X) has an effect on the variable Stress Levels Among Students (Y).